Design of a myoelectric prosthetic hand implementing postural synergy mechanically. Issue 5 (12th August 2014) - Li, Shunchong; Sheng, Xinjun; Liu, Honghai; Zhu, Xiangyang
Abstract : Purpose: – This paper aims to describe the design of a multi-degree of freedom (DOF) prosthetic hand prototype implementing postural synergy mechanically, which is actuated by two motors via a transmission unit, and is controlled using surface electromyography (sEMG) signal. Design/methodology/approach: – First, an anthropomorphic robotic hand is designed to imitate the human hand. The robotic hand has 18 DOF, 12 of which are actively driven by Bowden cables. Next, a set of different grasp modes are performed on a "full actuation" robotic hand, and principal component analysis (PCA) method is used to extract the first two postural synergies. Then, they are used to design a differential pulley-based transmission unit using two independent inputs to drive 12 output tendons. Finally, two control signals extracted from six channels of sEMG signals are used to proportionally control the two motors for achieving hand posture synthesis. Findings: – Using a differential pulley-based mechanical transmission unit to implement the synthesis of the first two postural synergies can make the prosthetic hand achieve different grasps by two motors, such as power, precision and lateral grasps. It is also feasible to control this "two actuation" prosthetic hand by relating the two-dimensional sEMG inputs with the first two postural synergies. Originality/value: – Mechanical implantation of postural synergies reduces the number of independent actuators without sacrificing the prosthetic hand's versatility and simplifies its controller. Two-dimensional control extracted from sEMG is mapped into the combination coefficients of postural synergy synthesis. It shows potential application in the practical prosthetic hand.